Peritoneal Carcinomatosis: A Multidisciplinary Approach - ceelen, wim.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Recent developments in regional and systemic anticancer therapies have improved the grim outlook of patients with peritoneal carcinomatosis (PC) from ovarian or gastrointestinal origin, leading to a renewed interest in both the underlying mechanisms at the origin of PC and the various therapeutic options. This is the first volume to provide a multidisciplinary approach to peritoneal carcinomatosis encompassing molecular mechanisms, histopathology, regional and systemic cytotoxic therapy, and surgical options. Peritoneal Carcinomatosis: A Multidisciplinary Approach will be of interest for medical, surgical and gynecological oncologists faced with the complexities of decision making in patients suffering from PC, as well as for basic and translational scientists active in the field of locoregional cancer spread. Numerous illustrations aid the reader throughout in the many facets of this disease. "Peritoneal Carcinomatosis remains a challenging consequence of cancer associated with significant morbidity. This often devastating condition benefits from a multidisciplinary approach to patient care. This text provides a detailed overview of the pathologic entities, biologic considerations and therapeutic approaches as viewed by experts in the field." Steven T. Rosen, M.D. Series Editor.
Peritoneal Carcinomatosis: Basic Concepts -- Structure and Function of Mesothelial Cells -- Molecular Biology of Peritoneal Carcinomatosis -- Role of Adhesion Molecules in Locoregional Cancer Spread -- Surgical Trauma, Minimal Residual Disease and Locoregional Cancer Recurrence -- Pseudomyxoma Peritonei Syndrome: Classification of Appendiceal Mucinous Tumours -- The Pathogenesis of Malignant Ascites -- Natural History of Peritoneal Carcinomatosis from Digestive Origin -- The Rationale for Intraperitoneal Heat and Drug Therapy -- Intraperitoneal Drug Therapy: Physical and Biological Principles -- Current Status of Intraperitoneal Antineoplastic Drug Delivery -- The Biologic Rationale of Hyperthermia -- Interactions between Hyperthermia and Cytotoxic Drugs -- Pharmacodynamic Aspects of Intraperitoneal Cytotoxic Therapy -- Cytoreductive Surgery for Peritoneal Carcinomatosis: Techniques and Methods -- Patient Selection for Cytoreduction and Hyperthermic Intraperitoneal Chemoperfusion -- Staging and Scoring of Peritoneal Carcinomatosis -- Peritonectomy Procedures -- Continuous Peritoneal Perfusion: Techniques, Methods and Applications -- Handling of Chemotherapeutic Drugs in the OR: Hazards and Safety Considerations -- Clinical Results of Surgery with or without Intraperitoneal Heated Drug Therapy -- Results of Cytoreduction followed by HIPEC in Carcinomatosis of Colorectal Origin -- HIPEC with Oxaliplatin in the Treatment of Peritoneal Carcinomatosis of Colorectal Origin -- Clinical Results of Cytoreduction and HIPEC in Pseudomyxoma Peritonei -- The Impact of Therapy in the Treatment of Pseudomyxoma Peritonei -- Clinical Results of Cytoreduction and HIPEC for Malignant Peritoneal Mesothelioma -- Cytoreduction and Intraperitoneal Chemotherapy for Carcinomatosis from Gastric Cancer -- Cytoreduction and Intraperitoneal Chemotherapy for Peritoneal Carcinomatosis of Ovarian Cancer -- The role of Neoadjuvant Chemotherapy versus Primary Surgery in the Management of Stage III Ovarian Cancer -- Morbidity and Quality of Life following Cytoreduction and HIPEC -- Detection and Treatment of Recurrent Disease after Cytoreduction and HIPEC -- Nonoperative and Multimodal Management of Peritoneal Carcinomatosis -- Systemic Chemotherapy in Patients with Peritoneal Carcinomatosis from Colorectal Cancer -- Systemic Chemotherapy in patients with Peritoneal Carcinomatosis from Non Colorectal Origin -- The Role of Radiotherapy in the treatment of Peritoneal Carcinomatosis -- Medical and Palliative Management of Malignant Ascites -- Experimental Approaches -- Targeted Intraabdominal Chemotherapy for Peritoneal Carcinomatosis -- Immunotherapy of Peritoneal Carcinomatosis -- Intraperitoneal Photodynamic Therapy -- Intraperitoneal Gene Therapy.
Keywords: Oncology .; Surgical oncology; Radiology; Oncology; Surgical Oncology; Imaging / Radiology